2002
DOI: 10.1093/aje/kwf018
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis and Meta-analysis of Glutathione S-Transferase M1 and Bladder Cancer: A HuGE Review

Abstract: Smoking is a known risk factor for bladder cancer. The product of the GSTM1 gene, glutathione S-transferase M1 (GSTM1), is involved in the detoxification of polycyclic aromatic hydrocarbons found in tobacco smoke; a homozygous deletion of this gene in approximately 50% of Caucasians and Asians results in a lack of GSTM1 enzyme activity. Most studies examining the relation between bladder cancer and GSTM1 have reported an increased risk associated with a lack of GSTM1 activity. The authors performed meta- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(123 citation statements)
references
References 121 publications
6
113
1
3
Order By: Relevance
“…The null genotype of GSTM1 and GSTT1 and GSTP Val/ Val genotype may lower the expression and activity of genotypes, and these genotypes are known to be associated with increasing incidence of certain cancers, such as head and neck, lung and bladder cancer (Benhamou et al, 2002;Engel et al, 2003;Hashibe et al, 2003). The main reason might be the inefficient carcinogen detoxification and therefore a higher risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The null genotype of GSTM1 and GSTT1 and GSTP Val/ Val genotype may lower the expression and activity of genotypes, and these genotypes are known to be associated with increasing incidence of certain cancers, such as head and neck, lung and bladder cancer (Benhamou et al, 2002;Engel et al, 2003;Hashibe et al, 2003). The main reason might be the inefficient carcinogen detoxification and therefore a higher risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] However, the results are not unequivocal. We have examined the association, if any, between GST genotypes with arsenic-induced skin lesions.…”
Section: Assessment Of the Role Of Selected Gst Genes Towards Susceptmentioning
confidence: 99%
“…24 Genetic variants of GST, alone or in combination with other genetic variations and environmental factors, were associated with a number of multifactorial diseases and conditions, such as smoking-related tumors, bladder cancer, colorectal cancer; esophageal cancer, myelodysplastic syndrome and leukemia, liver and renal diseases, and several other diseases like chronic obstructive pulmonary disease, bronchial asthma and solar keratosis. [25][26][27][28][29][30] GSTP1 is widely expressed in normal epithelium and is also involved in the detoxification of carcinogens in different tissues. 31,32 GSTP1 is overexpressed in tumors compared to normal tissues and has a role in cellular protection against oxidative stress.…”
mentioning
confidence: 99%
“…Individual case control studies, as well as pooled and meta analyses have confirmed this hypothesis to some extent, so that for example the deletion of GSTM1 variant was found to be associated with various cancer types, both alone and in combination with other genetic polymorphisms. [7][8][9][10] Careful analysis of the literature reveals a much more murky picture for the GSTT1 gene than for GSTM1. Although one group reported GSTT1 to be a risk factor for lung cancer, 11 the majority of studies have found no association between GSTT1 deletion and cancer as shown by a meta and pooled analysis, 12 and in general there are more negative findings for this variant than for the GSTM1 deletion.…”
mentioning
confidence: 99%